Who does it, pays it? Civil servants and personal liability - Rivero Ortega, Ricardo (Universidad Nacional del Litoral, 2020)
This paper explains the reasons to improve the regulation of personal liability of civil servants, balancing the legal security and public interest. The right understanding of the differences between criminal, administrative and accounting responsabilities is very important to achieve these goals and to prevent arbitrary power.